Answer:
x = 3
Explanation:
3^(5x - 9) = (1/27)^(2x-8)
3^(5x - 9) =(3^-3)^(2x-8)
3^(5x - 9) = 3^(-6x + 24)
So now you can solve for x since you have same base 3
5x - 9 = -6x + 24
11x = 33
x=3
3^5x-9= (1/27)^2x-8
Replace 1/27 = 1/3^3 = 3^-3
3^5x-9= (3^-3)^2x-8
a^b^c = a^(b*c)
3^5x-9= 3^(-3)*2x-8
Distribute
3^5x-9= 3^-6x+24
Since the bases are the same, the exponents are the same
a^b = a^c means b=c
5x-9= -6x+24
Add 6x to each side
5x+6x-9= -6x+6x+24
11x-9 = 24
Add 9 to each side
11x+9-9 = 24+9
Divide by 11
11x/11 = 33/11
6.5m questions
8.7m answers